2011
DOI: 10.1093/toxsci/kfr206
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability, Intracellular Mobilization of Nickel, and HIF-1α Activation in Human Lung Epithelial Cells Exposed to Metallic Nickel and Nickel Oxide Nanoparticles

Abstract: Micron-sized particles of poorly soluble nickel compounds, but not metallic nickel, are established human and rodent carcinogens. In contrast, little is known about the toxic effects of a growing number of Ni-containing materials in the nano-sized range. Here, we performed physicochemical characterization of NiO and metallic Ni nanoparticles and examined their metal ion bioavailability and toxicological properties in human lung epithelial cells. Cellular uptake of metallic Ni and NiO nanoparticles, but not met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
120
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(129 citation statements)
references
References 34 publications
8
120
1
Order By: Relevance
“…As described previously in rat pleural mesothelial cells [37] and human lung epithelial cells [38], Ni 2+ increased the level of HIF-1α (HIF1A) protein, which is important for SMC proliferation and vascular remodeling [39] under the normoxic conditions ( figure 3(b)). In addition, expression of downstream target genes of HIF-1α, including Vegfa, Adm1, Adm2 and Pdgfb [40,41], was markedly upregulated by Ni 2+ under normoxic conditions.…”
Section: N I 2+ Increases Hif-1α Levels In Arterial Smcssupporting
confidence: 52%
“…As described previously in rat pleural mesothelial cells [37] and human lung epithelial cells [38], Ni 2+ increased the level of HIF-1α (HIF1A) protein, which is important for SMC proliferation and vascular remodeling [39] under the normoxic conditions ( figure 3(b)). In addition, expression of downstream target genes of HIF-1α, including Vegfa, Adm1, Adm2 and Pdgfb [40,41], was markedly upregulated by Ni 2+ under normoxic conditions.…”
Section: N I 2+ Increases Hif-1α Levels In Arterial Smcssupporting
confidence: 52%
“…Recent studies have also shown that nano-sized Ni particles can sustain HIF-1a activity in human cell lines (47,48). Therefore, we hypothesized that ROS mediated the induction of HIF-1a and chemokines that were induced by NiNPs or the combination of NiNPs and PDGF in NRM2 cells.…”
Section: Discussionmentioning
confidence: 94%
“…In vitro experiments showed higher cytotoxicity of well-dispersed mesoporous silica and amorphous silica, dolomite, ZnO, Ni, Ag, and polystyrene NPs compared to the respective microparticles. [6][7][8][9][10][11][12][13][14][15] When particles smaller than 100 nm are compared, still-smaller particles act more toxically than larger ones (quantum dots, 16 TiO 2 17 ). In contrast to these studies, no differences have been reported for 10-100 nm silica particles compared to 45 µm ones, 18 and for nickel ferrite NPs.…”
Section: Cytotoxicitymentioning
confidence: 99%